Optimal operating method of gate and pump switching in water transfer project - Meng, Yujie; Wang, Weiping; Xu, Donglai; Qu, Shisong; Zhao, Weidong (Water science & technology. Water supply, 2023)
The Yellow River diversion project consists of three gates, two pumping stations, and one plain reservoir, with a total river length of 17.46 km in the Panzhuang Yellow River irrigation area, which provides the primary water source for the Dezhou central city, Shandong Province, China. The project is subject to the constraints of the Yellow River diversion sluice diverting water time, reservoir diverting water time, and combinations of pumping stations with self-flowing gates. The opening and closing forms of the gates and pumps are complicated and irregular, and the switching of the gates and pumps mainly depends on the experience of the staff, which makes the water transfer cost high and the water transfer time long. Based on engineering compositions in the study area, an optimal mathematical model is constructed by the dynamic programming method. By combining the flow and water level, the objectives of the minimum operation cost, the shortest water transfer time and the combination of the two are established. A new optimization scheme of the switch between gates and pumps combined with water level and flow is proposed, which reduces the operation cost by 20% and the water transfer time by 8%, providing an efficient operation mode.